Microbiome–Gut–Brain Axis: A Pathway for Improving Brainstem Serotonin Homeostasis and Successful Autoresuscitation in SIDS—A Novel Hypothesis - Praveen, Vijayakumar; Praveen, Shama (Frontiers in Pediatrics, 2017)
Sudden infant death syndrome (SIDS) continues to be a major public health issue. Following its major decline since the “Back to Sleep” campaign, the incidence of SIDS has plateaued, with an annual incidence of about 1500 SIDS related deaths in the United States, and thousands more throughout the world. The etiology of SIDS, the major cause of post neonatal mortality in the western world, is still poorly understood. Although sleeping in prone position is a major risk factor, SIDS continues to occur even in the supine sleeping position. The triple-risk model of Filiano and Kinney emphasizes the interaction between a susceptible infant during a critical developmental period, and stressor/s in the pathogenesis of SIDS. Recent evidence ranges from dysregulated autonomic control, to findings of altered neurochemistry, especially the serotonergic system that plays an important role in brainstem cardiorespiratory/thermoregulatory centers. Brainstem serotonin (5-HT) and tryptophan hydroxylase-2 (TPH-2) levels have been shown to be lower in SIDS, supporting the evidence that defects in the medullary serotonergic system play a significant role in SIDS. Pathogenic bacteria and their enterotoxins have been associated with SIDS, although no direct evidence has been established. We present a new hypothesis that, the infant’s gut microbiome and/or its metabolites, by its direct effects on the gut enterochromaffin cells (ECC), stimulates the afferent gut vagal endings by releasing serotonin (paracrine effect), optimizing auto-resuscitation by modulating brainstem 5-HT levels through the microbiome-gut-brain axis, thus playing a significant role in SIDS during the critical period of gut flora development and vulnerability to SIDS. The shared similarities between various risk factors for SIDS and their relationship with the infant gut-microbiome support our hypothesis. Comprehensive gut-microbiome studies are required to test our hypothesis.